2020
DOI: 10.1177/2156759x20957297
|View full text |Cite
|
Sign up to set email alerts
|

A Group Intervention for Prospective First-Generation College Students: Application With an Urban, African American Population

Abstract: We applied a qualitative inquiry to explore the experiences of African American youth engaging in a group intervention at an urban high school. Group topics were tailored to the needs of prospective first-generation college students to enhance youth social and academic capitol and identity strengthening. Experiences included changed perspectives and increased knowledge of the college-going experience that, in turn, increased participant sense of efficacy in completing college. We discuss implications for schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…For example, Mulhern's (2020) quasi-experimental analysis found that counselors had the greatest impacts on the high school graduation and college attendance rates of low-income students and those with low academic test scores. Qualitative research has also found that counselors play a pivotal role implementing interventions that widen access to and through college for marginalized student populations, including racially minoritized and first-generation youth (e.g., Arriero & Griffin, 2018;Malott et al, 2020).…”
Section: Influence On Student Outcomesmentioning
confidence: 99%
“…For example, Mulhern's (2020) quasi-experimental analysis found that counselors had the greatest impacts on the high school graduation and college attendance rates of low-income students and those with low academic test scores. Qualitative research has also found that counselors play a pivotal role implementing interventions that widen access to and through college for marginalized student populations, including racially minoritized and first-generation youth (e.g., Arriero & Griffin, 2018;Malott et al, 2020).…”
Section: Influence On Student Outcomesmentioning
confidence: 99%
“…Participants in this study facilitated an eight-session online counseling group designed to support college preparation for first-generation college students (Malott et al, 2020 ). Group topics were informed by evidenced-based practices, including suggestions specific to minoritized youth.…”
Section: Methodsmentioning
confidence: 99%
“…Group topics were informed by evidenced-based practices, including suggestions specific to minoritized youth. Topic examples include help-seeking, study skills, identity strengthening, and tactics in navigating oppressive campus settings or scenarios (Branch, 2018;Dennis et al, 2005;Gibbons & Shoffner, 2004;Green, 2015;Malott et al, 2020;Ishitani, 2006;Parnes et al, 2020;Tate et al, 2015). For a detailed overview of the group content, see (Malott et al, 2020).…”
Section: The Group Intervention and Membersmentioning
confidence: 99%
“…In turn, first-generation college students who take part in college preparatory interventions have shown improved attitudes and behaviors related to seeking support in college, which is essential for these students in persisting in postsecondary institutions (Schwartz et al, 2018). Such interventions can also help these students by enhancing their self-efficacy and confidence related to their personal beliefs about how successful they will be in college, and increasing their willingness to ask for help (Adams & McBrayer, 2020; Malott et al, 2020). Thus, the aim of this article is to describe the experience of first-generation college students participating in one such intervention on college preparation.…”
Section: Introductionmentioning
confidence: 99%
“…The present study embodies evidence-based school counseling principles (Zyromski & Dimmit, 2022); the intervention itself was developed based on results of initial focus groups with first-generation students enrolled in college, in which the students expressed the need for greater support in navigating the college preparatory and attendance process (Havlik et al, 2017). Further, it builds upon prior research that examined the use of this particular psychoeducational group with a Black/African American first-generation college student population (Havlik et al, 2020; Malott et al, 2020). Hence, the current study sought to broaden the scope of the intervention by applying sessions with Latine youth.…”
Section: Introductionmentioning
confidence: 99%